Reason at the Crossroads: Delving into the Tension of Be-lief and Awareness of Thinking Armada Riyanto's Per-spective - Bima Abdiono , Irenius; Armada Riyanto (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The purpose of this research is to explore the tension that exists between belief and conscious thinking. Life is often confronted with the rational and the irrational. Rational refers to conscious thinking (ratio), while irrational leads to belief (faith). Reason becomes a mediator to explain beliefs that are essentially difficult to understand by the ratio. Reason allows a dialog between belief and conscious thinking, so that it does not fall into lame understanding. Humans need to use their intellect to the fullest in order to arrive at an integral understanding of their beliefs. The method used in the research is qualitative method through literature study. This research found that the tension between belief and ratio is a natural thing, because the task of the ratio is to question or criticize so that humans do not fall into blind faith. Belief without ratio will actually lead to supertism, while reason without being based on faith will fall into nihilism and relativism. This research contributes to the harmonization of the two worlds of rational and irrational, as well as philosophical reflection as a way of finding holistic truth. Reason becomes the basic guideline in elaborating between belief and conscious thinking.